Peran Sekolah dan Orang Tua dalam Pembentukan Karakter pada Siswa Tuna Daksa di SLB Yasmin Sumenep - Felycia Rusfadia Sari; Evi Lailatus Sa'adah; Toifur Rahman (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore the roles of schools and parents in shaping the character of students with physical disabilities at SLB Yasmin Sumenep. Employing a qualitative descriptive approach through a case study method, data were gathered via interviews, classroom observations, and documentation. The findings reveal that schools play a significant role by providing accessible facilities, training teachers, and promoting an inclusive school culture. Teachers act as facilitators and guides, applying adaptive teaching strategies and instilling positive values. Meanwhile, parents serve as primary companions at home, fostering their children's confidence and independence. The collaboration between schools and families is essential to creating a supportive and effective learning environment. Despite challenges such as students’ physical limitations and emotional fluctuations, comprehensive support from all stakeholders contributes to the optimal development and character building of students with physical disabilities.